PENGARUH PEMBERIAN KOPI TERHADAP KUALITAS SPERMATOZOA TIKUS WISTAR JANTAN (Rattus norvegicus) YANG DIBERI PAPARAN ASAP ROKOK - Wantouw, Benny; Tendean, Lydia; Dja’afara, Ayu L. (Universitas Sam Ratulangi, 2015)
Abstract: Coffee contains caffeine which acts to increase cyclic adenosine monophosphate (cAMP) production in order to stimulate the motility of spermatozoa. Smoking affects the process of spermatogenesis, semen quality, and testosterone level. This study aimed to determine the effect of coffee on sperm quality of wistar rats exposed to cigarette smoke. This was a descriptive observational study. Samples were 6 wistar rats divided into 3 groups, each of 2 rats. The control group (P0) was exposed to cigarette smoke of 2 cigarettes/day. The P1 group was exposed to cigarette smoke (2 cigarettes/day) and was given 40 mg coffee solution; and the P2 group was exposed to cigarette smoke (2 cigarettes/day) and was given 80 mg coffee solution. The results showed that rats in P2 group showed increases and improvement in the spermatozoa concentration 70.9x106/ml, motility of spermatozoa category A by 55%, and morphologically normal spermatozoa by 55.5%. Conclusion: Coffee can improve the sperm quality of wistar rats Rattus norvegicus exposed to cigarette smoke.Keywords: cigarette, coffee, sperm qualityAbstrak: Kopi mengandung kafein yang berfungsi meningkatkan produksi siklik adenosin monofosfat (cAMP) yang merangsang gerakan spermatozoa. Rokok memengaruhi proses spermatogenesis, kualitas semen, dan kadar hormon testosteron. Penelitian ini bertujuan untuk mengetahui pengaruh kopi terhadap kualitas spermatozoa tikus wistar jantan yang diberi paparan asap rokok. Penelitian ini bersifat observasional deskriptif. Sampel sebanyak 6 ekor tikus wistar jantan: 2 ekor tikus wistar jantan sebagai kontrol (P0) yang hanya diberi paparan asap rokok 2 batang/hari; 2 ekor tikus wistar jantan diberi paparan asap rokok 2 batang/hari dan 40 mg larutan kopi (P1); dan 2 ekor tikus wistar jantan diberi paparan asap rokok 2 batang/hari dan 80 mg larutan kopi (P2). Hasil penelitian memperlihatkan pada kelompok P2 terjadi peningkatan konsentrasi spermatozoa sebesar 70,9x106/ml, peningkatan motilitas spermatozoa kategori A sebesar 55% dan morfologi normal spermatozoa sebesar 55,5%. Simpulan: Kopi dapat meningkatkan kualitas spermatozoa tikus wistar jantan Rattus norvegicus yang diberi paparan asap rokok.Kata kunci: rokok, kopi, kualitas spermatozoa